PEMELIHARAAN HAK ATAS TANAH DALAM ERA SERTIFIKAT ELEKTRONIK: ANALISIS KEPASTIAN HUKUM DAN PERLINDUNGAN HAK MASYARAKAT - Sofyatul Widad (SINERGI : Jurnal Riset Ilmiah, 2026)
The implementation of electronic land certificates is part of land administration reform aimed at improving efficiency, data accuracy, and legal certainty. However, this digital transformation has generated new issues, particularly concerning the maintenance of land rights after certification, such as risks of data updating errors, system failures, and inadequate legal protection for rights holders. This study formulates problems regarding the concept and mechanism of land rights maintenance within the electronic certificate system, the extent to which legal certainty is ensured, and the forms of legal protection available to the public. The research aims to analyze electronic-based land rights maintenance and to assess the level of legal certainty and protection of community rights. This study employs a normative legal research method using statutory, conceptual, and limited case approaches. The findings indicate that the maintenance of land rights through electronic certificates has not fully guaranteed legal certainty and continues to face normative, technological, and institutional challenges, highlighting the need for stronger regulations and clearer state responsibility in protecting land rights.